Optimisation of trabecular bone mimicking silicon-hydroxyapatite based composite scaffolds processed through selective laser melting - Ressler Antonia; Kamboj Nikhil; Ivanković Hrovoje; Hussainova Irina (Elsevier B.V., 2022)
Additive manufacturing is a rapid prototyping technology to produce complex three-dimensional scaffolds suitable for personalized medicine. In the present study, the laser powder bed fusion through a selective laser melting (SLM) approach has been applied to optimized fabrication of bio-mimicking scaffolds by using hydroxyapatite (HAp, 50 and 70 wt%) and silicon powder mixture. In situ formation of pseudo-wollastonite (P–W, CaSiO3) has been detected along with silicon for 50 wt% of HAp powder mixture, while an increase in HAp content has resulted in P–W, silicon and larnite (Ca2SiO4) formation. The pore size of 400 μm, according to the CAD model, are observed at the scaffolds fabricated at the shortest exposure time (50 μs), lowest laser current (500 mA) and energy density (41.6 J/mm3), and simultaneously at the highest scanning speed. Compressive stress demonstrated by the fabricated scaffolds is shown to be acceptable for their use in metaphyseal region of long bones.